Apathy is associated with white matter network disruption and specific cognitive deficits in Parkinson's disease. Issue 2 (11th January 2022) - Wen, Ming-Ching; Thiery, Alexandre; Tseng, Wen-Yih Isaac; Kok, Trina; Xu, Zheyu; Chua, Shu Ting; Tan, Louis C.S.
Abstract: Background: Apathy is common in Parkinson's disease (PD) but its underlying white matter (WM) architecture is not well understood. Moreover, how apathy affects cognitive functions in PD remains unclear. We investigated apathy-related WM network alterations and the impact of apathy on cognition in the context of PD. Methods: Apathetic PD patients (aPD), non-apathetic PD patients (naPD), and matched healthy controls (HCs) underwent brain scans and clinical assessment. Graph-theoretical and network-based analyses were used for group comparisons of WM features derived from diffusion spectrum imaging (DSI). Path analysis was used to determine the direct and indirect effects of apathy and other correlates on different cognitive functions. Results: The aPD group was impaired on neural integration measured by global efficiency ( p = 0.009) and characteristic path length ( p = 0.04), executive function ( p < 0.001), episodic memory ( p < 0.001) and visuospatial ability ( p = 0.02), and had reduced connectivity between the bilateral parietal lobes and between the putamen and temporal regions ( p < 0.05). In PD, executive function was directly impacted by apathy and motor severity and indirectly influenced by depression; episodic memory was directly and indirectly impacted by apathy and depression, respectively; conversely, visuospatial ability was not related to any of these factors. Neural integration, though being marginally correlated with apathy, was not associated with cognition. Conclusions: Our results suggest compromised neural integration and reduced structural connectivity in aPD. Apathy, depression, and motor severity showed distinct impacts on different cognitive functions with apathy being the most influential determinant of cognition in PD.